Increased Severity and Mortality of CAP in COPD: Results from the German Competence Network, CAPNETZ - Braeken, Dionne C.W. (Chronic Obstr Pulm Dis, 2015)
Background:Mortality of community acquired pneumonia (CAP) remains high despite significant research efforts. Knowledge about comorbidities including chronic obstructive pulmonary disease (COPD) might help to improve management and ultimately, survival. The impact of COPD on CAP severity and mortality remains a point of discussion. Objectives:Assess the prevalence and clinical characteristics of COPD in the observational German Competence Network for CAP, CAPNETZ, and to study the impact of COPD on CAP severity and mortality. Methods:1307 consecutive patients with CAP (57.0% males, age 59.0±18.5), classified as CAP-only (n=1043; 78.0%) and CAP-COPD (n=264; 20.2%) were followed up for 180 days. Associations between CAP, COPD and mortality were evaluated by univariate/multivariate and Kaplan-Meier survival analyses. Results:CAP-COPD patients were older, more often males, current/former smokers, with higher confusion-urea-respiratory rate-blood pressure, (CURB) scores. Length of hospital stay, urea, glucose and leucocytes plasma levels, and arterial carbon dioxide tension (PaCO(2)) were significantly increased in CAP-COPD. Thirty, 90- and 180-day mortality rates were significantly increased in CAP-COPD (p=0.046, odds ratio [OR]=2.48, 95% confidence interval [CI] 1.015-6.037; p=0.003, OR=2.80, 95%CI 1.430-5.468; p=0.001, OR=2.57, 95%CI 1.462-4.498; respectively). Intensive care unit (ICU)-admission and age, but not COPD, were identified as independent predictors of short- and long-term mortality. Conclusion:Severity as well as mortality was significantly higher in COPD patients with CAP. To improve CAP management with the aim to decrease its still-too-high mortality, underlying comorbidities, particularly COPD, need to be assessed.